Current account imbalances and real exchange rates in the Euro area - Michael G. Arghyrou; Georgios Chortareas (Cardiff University, Cardiff Business School, 2006)
Global current account imbalances have been one of the focal points of interest for policymakers during the last few years. Less attention has been paid, however, to the diverging current account balances of the individual euro area countries. In this paper we consider the dynamics of current account adjustment and the role of real exchange rates in current account determination in the EMU. After controlling for the effects of income growth, we find the relationship between real exchange rates and the current account to be substantial in size and subject to non-linear effects. Overall, we argue that real exchange rates can offer further insights, beyond the effects of the income catch-up process, relevant to current account determination in the EMU.
Keywords: C51; C52; F31; F32; F41; 330; current account; real exchange rate; EMU; nonlinearities